Milled rapeseeds and oats decrease milk saturated fatty acids and ruminal methane emissions in dairy cows without changes in product sensory quality - Halmemies-Beauchet-Filleau, Anni; Jaakkola, Seija; Kokkonen, Tuomo; Turpeinen, Anu M.; Givens, D. Ian; Vanhatalo, Aila (Frontiers in Animal Science, 2023)
Plant lipids in the diet are known to modify milk fatty acid (FA) composition and to mitigate ruminal methane emissions. The objective of the present work was to examine the potential of milled rapeseeds and oats to decrease both milk saturated FA and ruminal methane emissions at practical farm conditions. In the pilot study, six Finnish Ayrshire cows were fed a control diet for 3 weeks followed by a lipid-rich test diet of 3 weeks. Experimental diets were based on grass silage supplemented with barley and rapeseed meal in the control diet, and with oats and milled rapeseeds in the test diet. Lipid inclusion rate was 55 g/kg dry matter (DM). In the main study, the whole Finnish Ayrshire research herd in milk (n=49-59) was used in a switch-back designed study. The cows were fed a control diet for 3 weeks, then a test diet for 4 weeks and finally control diet for 3 weeks. The diets were the same as in the pilot study except for lower lipid inclusion level of 50 g/kg DM. Test diet decreased DM intake by 15% and energy-corrected milk (ECM) yield by 13% in the pilot study. The adjustment of supplemental lipids from 55 to 50 g/kg DM was successful as the DM intake decreased only by 4% relative to control diet in the main study. Furthermore, the yields of milk, lactose, protein, and fat were also unaffected by dietary lipids in the main study. Milk fat was significantly altered in both studies. Milk fat saturated FA were decreased by 16-20% in the test diet, mainly due to the de novo FA of 6-to 16-carbon (reduction of 22-48%). Milk fat cis-9 18:1 was increased by 63-78% in the test diet relative to control. Dairy products' (milk, butter, cheese) organoleptic quality was not compromised by modified lipid profile. Ruminal methane and hydrogen intensities (n=23, g or mg/kg ECM) were 20 and 39% lower, respectively on test diet relative to control. This reduction can be attributed to lower amount of organic matter fermented in the rumen as indicated by lower DM intake and nutrient digestibility.